Entrepreneurship Empowerment Strategy in Islamic Boarding Schools: Lesson from Indonesia - Naimah; Rahman, Ainur; Ismail, Zawawi; Sulaiman, Hamidah Binti; Kalupae, Abdulaziz (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
Compared to formal educational institutions, Islamic boarding schools have their uniqueness and many advantages. Today's Islamic boarding schools provide learning about religious knowledge and entrepreneurship to equip and provide independence when returning to the community. This study aims to analyze the types of entrepreneurial empowerment of students and analyze the strategies of the Nurul Ulum Islamic Boarding School in Kemuningsari Lor Village, Panti District, Jember Regency in empowering santri entrepreneurship. The research method used is descriptive qualitative. While the data collection techniques used were observation, interviews, and documentation. The study results show that the types of entrepreneurial empowerment activities that are managed and developed by the pesantren are adapted to the conditions of the pesantren environment, infrastructure, and capabilities possessed by the pesantren. First, the generated businesses result from waste management (making cellphone bags, handkerchiefs, school bags, and brooches). Second, dress code (sewing) in clothes, headscarves, coats, and pants. Then, the entrepreneurial strategies implemented at the Nurul Ulum Islamic Boarding School include cost leadership, differentiation strategies, and focus strategies. This research contributes in-depth knowledge that Islamic boarding schools play an essential role in entrepreneurship in providing new jobs and poverty alleviation and contributing to the country's economic development.